2008
DOI: 10.3329/bjp.v2i2.570
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of amlodipine in oxidative stress induced by experimental myocardial infarction in rats

Abstract: The present study investigated whether the administration of amlodipine ameliorates oxidative stress induced by experimental myocardial infarction in rats. Adrenaline was administered and myocardial damage was evaluated biochemically [significantly increased serum aspertate aminotransferase (AST), lactate dehydrogenase (LDH) and malondialdehyde (MDA) levels of myocardial tissue] and histologically (morphological changes of myocardium). Amlodipine was administered as pretreatment for 14 days in adrenaline treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Drug doses were guided by the literature and adjusted through pilot trials. NAC was given in a dose of 300 mg/kg/day (Abla et al, 2005, Hsieh et al, 2014), amlodipine was given in a dose of 10 mg/kg/day (Begum and Akhter, 2007), lisinopril was given in a dose of 20 mg/kg/day (Albarwani et al, 2015), and allopurinol was given in a dose 50 mg/kg/day (Aldaba-Muruato et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Drug doses were guided by the literature and adjusted through pilot trials. NAC was given in a dose of 300 mg/kg/day (Abla et al, 2005, Hsieh et al, 2014), amlodipine was given in a dose of 10 mg/kg/day (Begum and Akhter, 2007), lisinopril was given in a dose of 20 mg/kg/day (Albarwani et al, 2015), and allopurinol was given in a dose 50 mg/kg/day (Aldaba-Muruato et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Some other investigators demonstrated the cardioprotective effect of amlodipine in oxidative stress induced by experimental myocardial infarction in rats. Here, amlodipine significantly decreased serum AST and LDH levels and protected the myocardium from adrenalin induced myocardial injury [17].…”
Section: Introductionmentioning
confidence: 79%
“…Our result is in agreement with other investigators findings. Previously (14,15) found significantly elevated biochemical parameters after the inoculation of adrenaline. Our results are also according to (16) that showed a highly significant elevation in the cardiac biomarkers.…”
Section: Discussionmentioning
confidence: 94%